DETERMINANTS OF THE ANALYSIS MODEL OF ZAKAT ACCOUNTING IN INCREASING ACCOUNTABILITY IN MEDAN CITY LAZISMU - Yustriawan, Dian; Ritonga, Pandapotan; Tussadiyah, Halimah; Alamsyah, Yoga; Sebayang, Nasha Fitriadi (Proceeding International Seminar of Islamic Studies, 2024)
The accountability of a zakat institution will directly affect the level of muzzaki's trust in paying zakat. Accountability will be realized one way by presenting the institution's financial reports in accordance with applicable standards. The standard for presenting financial reports for zakat institutions refers to PSAK number 109. The purpose of this research is to find out how zakat accounting improves the accountability of LAZISMU Medan City. The method used in this study is qualitative and the source of the data was generated from a direct interview process with the management of LAZISMU Medan City in the finance department. The data requested includes financial reports in the form of zakat receipts and their distribution. In presenting the financial statements it is indicated that LAZISMU has not fully implemented PSAK standard number 109, this will have an impact on accountability which causes zakat receipts to be not optimal. To overcome this, it is necessary to conduct training for human resources in LAZISMU Medan City, preferably those who are responsible for the institution's financial reports.